Analisis Dampak Sosial, Ekonomi, dan Lingkungan Budidaya Ikan Keramba Jaring Apung (KJA) sebagai Implementasi Program CSR PT Pertamina Patra Niaga AFT SMB II di Kampung Sugihwaras, Kota Palembang: Analysis of Social, Economic, and Environmental Impacts of Floating Net Cage Aquaculture as the Implementation of CSR Program by PT Pertamina Patra Niaga AFT SMB II in Kampung Sugihwaras, Palembang City - Gentur Sutopo, Sigit; Dyah Istiqlawati, Savira; ayu, sevina; Ria Safitri, Ananta; Ramadani Andelia, Siti (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2025)
The exploitation of natural resources, particularly small-scale mining, often causes social, economic, and environmental impacts if not managed sustainably. In Sukarami District, clay mining for brick production has led to environmental degradation, social conflicts, and economic pressure. To address these issues, PT Pertamina Patra Niaga AFT Sultan Mahmud Badaruddin II, through its Lentera Talang CSR program, initiated community empowerment activities by developing freshwater fish farming using floating net cages (KJA) in former mining pits. This program aims to restore the environment while improving community welfare. This study analyzes the social, economic, and environmental impacts of KJA activities as part of CSR implementation in Kampung Sugihwaras, Palembang. The results show that socially, the program enhances community engagement, fosters self-reliance, serves as a post-mining empowerment model, and reduces accident risks at mining sites. Economically, it creates jobs, increases income, and encourages local business development and economic diversification. Environmentally, it promotes the productive use of abandoned mining land, supports aquatic ecosystem rehabilitation, reduces water pollution, and mitigates eutrophication risks.